Outsourcing Equality: Migrant Care Worker Imaginary in Finnish Media - Nordberg, Camilla (Nordic Journal of Working Life Studies, 2016)
Implications from the restructuring of Nordic eldercare include the incorporation of new categories of care workers and a redefinition of the terms of citizenship and participation in working life. Drawing on the idea that policy actors script care worker subjectivities, this article examines print media as a key arena where the cultural imaginary of care work is played out. The media has the potential to accommodate ideological complexity through the possible range of participatory actors. From the scripts promoted through the mediascape, we can learn about the positions understood as being (in)appropriate for migrant care workers. This study draws on the analysis of news and feature stories from 2003 to 2013 in the largest Finnish daily, Helsingin Sanomat, and in the periodical Kuntalehti, published by the Finnish Association of Local and Regional Authorities. The article points to tensions in Finnish media discourse, identifying ambiguous occupational scripts for migrant care workers—rooted in neoliberal repertoires of self-sufficiency and normative individualism on the one hand and helplessness and naivety on the other hand. It draws attention to an unsettling construction whereby migrant care workers are excluded from a long-term contract with the Finnish care labor market, and where social equality is conditioned to global redistribution.